Countryside education: a look at the educational policy cycle approach (Research, Society and Development, 2020)
Public educational policies linked to urban and rural areas have solid boundaries, and for many years, Countryside Education has been relegated to marginal spaces in the design and implementation of such policies. Thus, this article aims to describe and analyze public policies for Countryside Education through the Policy Cycle Approach (Mainardes, 2006). The research methodology is based on the qualitative approach (Stake, 2011), of documentary type (Oliveira, 2008). The documents analyzed in this study constitute a primary source of research, since they are the object of the researcher's view and do not act as a theoretical reference. After processing the documents, it can be observed that Countryside Education has been conquering more space in the scope of public policies, being possible to perceive strong influence of social movements in the fight for an education for the rural area population, which have been translated into regulatory frameworks that guide and regulate educational policies for countryside education.